Pendampingan Mahasiswa Prodi PKAUD dalam Pelaksanaan Magang di TK Embun Pagi Tampo, Mengkendek, Tana Toraja, Sulawesi Selatan - Serdianus Serdianus; Linda Ari (Jurnal Informasi Pengabdian Masyarakat, 2024)
Internships are pivotal in bridging theoretical knowledge and practical application for students. Engaging in internships allows students to apply their acquired classroom knowledge to real-world scenarios. Ensuring the success of these internships necessitates intensive guidance. The internship mentoring process comprises three stages: preparation, monitoring, and evaluation—the outcomes of this mentoring exhibit the successful implementation of student internships at TK Embun Pagi Tampo. Students gained valuable experiences in teaching strategies, classroom management, and supporting early childhood education. Moreover, the internship program honed students' practical skills pertinent to the learning processes in early childhood education